Second-Generation RT-QuIC Assay for the Diagnosis of Creutzfeldt-Jakob Disease Patients in Brazil - Barbosa, Breno José Alencar Pires; Castrillo, Bruno Batitucci; Alvim, Ricardo Pires; de Brito, Marcelo Houat; Gomes, Helio R.; Brucki, Sônia M. D.; Smid, Jerusa; Nitrini, Ricardo; Landemberger, Michele C.; Martins, Vilma R.; Silva, Jerson L.; Vieira, Tuane C. R. G. (Frontiers in Bioengineering and Biotechnology, 2020)
The recent development of IQ-CSF, the second generation of real-time quaking-induced conversion (RT-QuIC) using cerebrospinal fluid (CSF), for the diagnosis of Creutzfeldt-Jakob Disease (CJD) represents a major diagnostic advance in the field. Highly accurate results have been reported with encouraging reproducibility among different centers. However, availability is still insufficient, and only a few research centers have access to the method in developing countries. In Brazil, we have had 603 suspected cases of CJD since 2005, when surveillance started. Of these, 404 were undiagnosed. This lack of diagnosis is due, among other factors, to the lack of a reference center for the diagnosis of these diseases in Brazil, resulting in some of these samples being sent abroad for analysis. The aim of this research study is to report the pilot use of IQ-CSF in a small cohort of Brazilian patients with possible or probable CJD, implementing a reference center in the country. We stored CSF samples from patients with possible, probable or genetic CJD (one case) during the time frame of December 2016 through June 2018. All CSF samples were processed according to standardized protocols without access to the clinical data. Eight patients presented to our team with rapidly progressive dementia and typical neurological signs of CJD. We used CSF samples from seven patients with other neurological conditions as negative controls. Five out of seven suspected cases had positive tests; two cases showed inconclusive results. Among controls, there was 1 false-positive (a CSF sample from a 5-year-old child with leukemia under treatment). The occurrence of a false positive in one of the negative control samples raises the possibility of the presence of interfering components in the CSF sample from patients with nonneurodegenerative pathologies. Our pilot results illustrate the feasibility of having CJD CSF samples tested in Brazilian centers and highlight the importance of interinstitutional collaboration to pursue a higher diagnostic accuracy in CJD in Brazil and Latin America.